Inhaled isoflurane via the anaesthetic conserving device versus propofol for sedation of invasively ventilated patients in intensive care units in Germany and Slovenia: an open-label, phase 3, randomised controlled, non-inferiority trial. Issue 11 (November 2021) - Meiser, Andreas; Volk, Thomas; Wallenborn, Jan; Guenther, Ulf; Becher, Tobias; Bracht, Hendrik; Schwarzkopf, Konrad; Knafelj, Rihard; Faltlhauser, Andreas; Thal, Serge C; Soukup, Jens; Kellner, Patrick; et al.
Summary: Background: Previous studies indicate that isoflurane could be useful for the sedation of patients in the intensive care unit (ICU), but prospective studies evaluating isoflurane's efficacy have been small. The aim of this study was to test whether the sedation with isoflurane was non-inferior to sedation with propofol. Methods: This phase 3, randomised, controlled, open-label non-inferiority trial evaluated the efficacy and safety of up to 54 h of isoflurane compared with propofol in adults (aged ≥18 years) who were invasively ventilated in ICUs in Germany (21 sites) and Slovenia (three sites). Patients were randomly assigned (1:1) to isoflurane inhalation via the Sedaconda anaesthetic conserving device (ACD; Sedana Medical AB, Danderyd, Sweden; ACD-L [dead space 100 mL] or ACD-S [dead space 50 mL]) or intravenous propofol infusion (20 mg/mL) for 48 h (range 42–54) using permuted block randomisation with a centralised electronic randomisation system. The primary endpoint was percentage of time in Richmond Agitation–Sedation Scale (RASS) range –1 to –4, assessed in eligible participants with at least 12 h sedation (the per-protocol population), five or more RASS measurements, and no major protocol violations, with a non-inferiority margin of 15%. Key secondary endpoints were opioid requirements, spontaneous breathing, time to wake-up and extubation, and adverse events. Safety was assessed in all patients who received at least one dose. The trial is complete and registered with EudraCT, 2016–004551–67. Findings: Between July 2, 2017, and Jan 12, 2020, 338 patients were enrolled and 301 (89%) were randomly assigned to isoflurane (n=150) or propofol (n=151). 146 patients (97%) in each group completed the 24-h follow-up. 146 (97%) patients in the isoflurane group and 148 (98%) of patients in the propofol group were included in the per-protocol analysis of the primary endpoint. Least-squares mean percentage of time in RASS target range was 90·7% (95% CI 86·8–94·6) for isoflurane and 91·1% (87·2–95·1) for propofol. With isoflurane sedation, opioid dose intensity was 29% lower than with propofol for the overall sedation period (0·22 [0·12–0·34] vs 0·32 [0·21–0·42] mg/kg per h morphine equivalent dose, p=0·0036) and spontaneous breathing was more frequent on day 1 (odds ratio [OR] 1·72 [1·12–2·64], generalised mixed linear model p=0·013, with estimated rates of 50% of observations with isoflurane vs 37% with propofol). Extubation times were short and median wake-up was significantly faster after isoflurane on day 2 (20 min [IQR 10–30] vs 30 min [11–120]; Cox regression p=0·0011). The most common adverse events by treatment group (isoflurane vs propofol) were: hypertension (ten [7%] of 150 vs two [1%] of 151), delirium (eight [5%] vs seven [5%]), oliguria (seven [5%] vs six [4%]), and atrial fibrillation (five [3%] vs four [3%]). Interpretation: These results support the use of isoflurane in invasively ventilated patients who have a clinical need for sedation. Funding: Sedana Medical AB.